"Mapping" Media Spaces: Smoothness, Striation, and the Expropriation of Desire in American Journalism from Postindustrial to Datafied Capitalism. Issue 4 (1st October 2018) - Fitzgerald, Andrew Arthur
Abstract: The future of journalism in the digital age is a major topic of both vocational and academic debate—as is the question of whether anything is "new" with the rise of the digital more broadly. This article argues for a redeployment of Deleuze and Guattari's concepts of "smooth" and "striated" space. Conducting a synthesis of a new wave of scholarship on digital journalism with the body of "sociology of news" literature from the late 1970s and 1980s, it maps continuities and intensifications of processes in the interplay between journalistic desire and the constraints of liberal capitalism, while also noting a key shift in the relationship between journalism and dominant economic classes, concomitant with a new form of "datafied capitalism."